Analysis Of The Financial Performance Of The Regional Government Of Sidenreng Rappang Regency Before And After Obtaining Fair Opinion Without Exemption (WTP) - Anwar Talib; Hasriana Sabri; Akhsan Akhsan (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine a comparison of the financial performance of the regional government of Sidenreng Rappang district based on the independence ratio, effectiveness ratio, efficiency ratio, spending harmony ratio, and growth ratio. The data collection technique used in this study is Documentation. The data analysis technique in this study is a quantitative descriptive technique and analysis of financial performance ratios in the form of independence ratios, effectiveness ratios, efficiency ratios, spending harmony ratios, and growth ratios. The results showed that the level of independence indicated that Sidenreng Rappang District before and after WTP was categorized as instructive independence or where the role of the central government was still dominant compared to the role of the regions themselves. The effectiveness ratio shows that Sidenreng Rappang District before WTP and after WTP is categorized as ineffective because the average value is below 100%, this shows that the financial performance of Sidenreng Rappang Regency has not been able to achieve the goals or targets that have been set or planned. The efficiency ratio shows that Sidenreng Rappang District before WTP and after WTP is categorized as Efficient, this shows that the local government has been careful in calculating the costs incurred. The growth ratio shows that the percentages of Sidenreng Rappang Before WTP and After WTP experienced unstable percentages because the available data was still fluctuating. This is caused by the target factor and the realization of regional income receipts that vary each year. From the results of the study it is said that the hypothesis Ha is accepted and Ho is rejected or there is no difference in the financial performance of the Regional Governments before and after WTP in Sidenreng Rappang Regency.